Swinging calcified amorphous tumour in the ascending aorta. (1st July 2022) - Sokolowski, Caleb; Baciewicz, Frank
Abstract: A 70-year-old woman with heart failure and end-stage renal disease on dialysis was found to have a 2.9 cm × 0.9 cm swinging mass attached to the posterior wall of the ascending aorta, 3 cm above the aortic valve. Due to the risk of embolization, she underwent an aortotomy and mass excision. The mass had extensive calcifications with degenerative changes and no evidence of malignancy. This represents an exceedingly rare location for a calcified amorphous tumour. Our review adds to the literature establishing the proximal aorta as a characterized location for a calcified amorphous tumour and provides a treatment approach to prevent embolization. Abstract : Calcified amorphous tumour (CAT) was originally characterized in 1997 by Reynolds et al. [1] as an intracavitary mass consisting of calcification and fibrous material.